Dating violence and the stay/leave decisions of young women in college - Lyon, Sarah Elizabeth (Kansas State University, 2014)
Ending a college dating relationship is common as college coeds begin trying on romantic relationships for size. Ending the relationship because the relationship has become violent can add more complexities to an already unpleasant task. This study was an attempt to better understand the stay/leave decisions for college women who were victims of dating violence and whether or not these decisions differed for college women who were involved in violent versus non-violent dating relationships. Structural equation modeling was used to explore the factors that influenced the likelihood of female college students’ dating relationships to end using Choice and Lamke’s (1999) two-part decision-making model. In summary, victims reported greater relationship distress, less attraction towards someone other than their partner, less relationship safety, lower relationship efficacy, less social support, and fewer good friends than non-victims. Results also indicated that college women’s consideration of “Will I be better off?” was more important in the decision to leave a dating relationship than their perception of “Can I do it?” In addition, results from Multiple Indicators Multiple Causes (MIMIC) modeling found that, while victims believed they were more likely to be better off leaving their violent, dating partners, they felt less able to actually leave the relationship than their non-victim counterparts. MIMIC modeling also found that being a victim or not of dating violence did not predict breakup directly. These findings have important implications for prevention and treatment of dating violence and can be used to further the research in the area of dating violence, college students, and stay/leave decisions.
Keywords: Dating violence; Stay/leave decisions; College students; Women; Dating relationships; Breakup; Behavioral Sciences (0602); Individual & Family Studies (0628); Women's Studies (0453)